1998
DOI: 10.1128/aem.64.10.3917-3922.1998
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Activity of Campylobacter jejuni Far below the Minimal Growth Temperature

Abstract: The behavior of Campylobacter jejuni at environmental temperatures was examined by determining the physiological activities of this human pathogen. The minimal growth temperatures were found to be 32 and 31°C for strains 104 and ATCC 33560, respectively. Both strains exhibited a sudden decrease in growth rate from the maximum to zero within a few degrees not only near the maximal growth temperature but also near the minimal growth temperature. This could be an indication that a temperature-dependent transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(112 citation statements)
references
References 41 publications
7
103
1
1
Order By: Relevance
“…in Hamilton soil, E. coli were only recovered down to 5 cm but C. jejuni were recovered down to 15 cm -E. coli results will be presented elsewhere). We speculate that C. jejuni actively moved through soil water films as these bacteria are very motile and able to move towards favourable environments (Hazeleger et al 1998). This movement was most clearly seen in Horotiu soil probably because this soil was the most favourable for survival and C. jejuni numbers remained above the limit of detection in lower core sections for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…in Hamilton soil, E. coli were only recovered down to 5 cm but C. jejuni were recovered down to 15 cm -E. coli results will be presented elsewhere). We speculate that C. jejuni actively moved through soil water films as these bacteria are very motile and able to move towards favourable environments (Hazeleger et al 1998). This movement was most clearly seen in Horotiu soil probably because this soil was the most favourable for survival and C. jejuni numbers remained above the limit of detection in lower core sections for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of meat type, Campylobacter spp. do not usually grow outside of their host and never at temperatures below 30 °C (Hazeleger et al, 1998). Moreover, inoculation studies suggest that Campylobacter spp.…”
Section: Bacterial Hazards That May Be Influenced By Chilling Time-tementioning
confidence: 99%
“…However, Campylobacter spp. have been reported to survive in water, at low temperatures, for up to 4 months (Rollins and Colwell 1986;Buswell et al 1998;Hazeleger et al 1998), during processing (Cools et al 2005) and in the environment generally (Park 2002). Therefore, survival mechanisms other than those commonly found in other organisms (like two-component regulators) may be important.…”
Section: General Survival Mechanisms In Enteric Bacteriamentioning
confidence: 99%
“…Lazaro et al (1999) demonstrated motility, oxygen consumption, protein synthesis and survival of C. jejuni at 4°C. Strains have also been demonstrated to exhibit a sudden decrease in growth rate from the maximum to zero within a few degrees not only near the maximal growth temperature, but also near the minimum growth temperature (Hazeleger et al 1998). This suggests that C. jejuni does elicit a cold shock response that regulates gene expression at low temperatures.…”
Section: Survival Of Cold Stressmentioning
confidence: 99%